Exploring the behavioural dynamics of tax incentives: A cross-disciplinary theoretical and practical review - Harish, M; Shah, C S Ankit; Poonam, Poonam; Kushwaha, Sumit (The International tax journal, 2026)
Tax incentives are widely used policy instruments designed to motivate individuals and firms toward desired economic behaviours, yet their actual impact depends less on the incentive itself and more on how taxpayers psychologically interpret it. This paper examines the behavioural dynamics underlying tax incentives through a cross-disciplinary review that integrates insights from economics, behavioural psychology, decision science, and public policy. Rather than viewing taxpayers as purely rational agents responding to financial gains, the review highlights the role of cognitive biases, mental accounting, fairness perceptions, compliance norms, and risk framing in shaping responses to deductions, credits, exemptions, rebates, and preferential rates. The study synthesizes empirical and theoretical findings across these domains to uncover why similar incentives trigger different behaviours across demographic groups, economic environments, and institutional systems. It also evaluates practical evidence from real-world tax administrations, identifying where incentives succeed, underperform, or produce unintended distortions. The review concludes that understanding behavioural mechanisms is essential for designing effective, equitable, and sustainable tax incentive systems that align policy intentions with actual taxpayer behaviour.